Transdifferentiation of Myoblasts Into Adipocytes by All-Trans-Retinoic Acid in Avian - Kim, Dong-Hwan; Lee, Joonbum; Suh, Yeunsu; Ko, Jae-Kyun; Lee, Kichoon (Frontiers in Cell and Developmental Biology, 2022)
Increased adipogenesis in muscle tissues is related to metabolic syndromes and muscle weakness in humans, and improvement of meat quality in animal production. With growing evidence for pro-adipogenic functions of all-trans retinoic acid (atRA), the current study investigated whether atRA can transdifferentiate myoblasts into adipocytes using a quail myogenic cell line (QM7) and avian primary myoblasts. atRA increased cytoplasmic lipid droplet accumulation and mRNA expression for adipogenic genes in these cells. Acute induction of Pparg expression by atRA under cycloheximide treatment indicated direct regulation of Pparg by atRA. In addition, the induction of Pparg expression was mediated by retinoic acid receptor (RAR). At high levels of Pparg by atRA, BADGE, an antagonist of PPARg, inhibited, and rosiglitazone, an agonist of PPARg, further enhanced atRA-induced transdifferentiation. However, at the very low levels of Pparg in the absence of atRA treatment, rosiglitazone could not induce transdifferentiation of avian myoblasts. These data suggest that induction of Pparg expression by atRA is an essential molecular event in myoblasts for atRA-induced transdifferentiation into adipocytes. Based on our findings, atRA can be a new transdifferentiation factor of myoblasts to adipocytes, providing a potential nutrient to enhance marbling in poultry.